Child and family law: Trinidad and Tobago - Daly, Stephanie ([s.n.] [S.l.], 1992)
Identifies the gaps of all the laws relating to the child in the light of the United Nations Convention on the Rights of the Child. Makes recommendations relevant to the ratification of that Convention. Examines the laws relating to the child and family for possible reform or amendment.